Munigua, Spanien. Die Arbeiten der Jahre 2017 und 2018 - Schattner, Thomas G.; Ruipérez, H.; Schäffler, D. (e-Forschungsberichte des DAI, 2019)
As part of the current research program "Preliminary Studies for a New Reconstruction of Munigua", the work and research in the period under consideration was concentrated on the Terrace Sanctuary, the Podium Temple, the Double Storey Hall and the Streets. In all these cases, plans were drawn and the existing graphic documentation was completed. This was done primarily through the Structure from Motion technology (SfM), but occasionally also by hand in the well-known tradition.